Hubungan Keteraturan Antenatal Care pada Ibu Hamil Trimester III dengan Kejadian Pre Eklamsia di Puskesmas Banjarsengon kabupaten Jember. - Nur Perdani, Ayu Puteri (Program Studi Keperawatan dan Kesehatan, Sekolah Tinggi Ilmu Kesehatan (STIKES) Bhakti Al-Qodiri, 2020)
Antenatal care is one form of health services for pregnant women which if done regularly can reduce both maternal and infant mortality rates, by conducting regular antenatal care it is expected that pregnant women and fetuses can be monitored for their development by health workers. This study aims to determine the relationship of regular antenatal care in third trimester pregnant women with the incidence of Pre-eclampsia in Banjarsengon Health Center, Jember Regency. This study uses a quantitative research design with a cross-sectional approach. Respondents in this study were 20 people with purposive sampling data collection techniques. Data were analyzed using exact fisher. The results of this study found that there is a relationship between regular Antenatal care in Trimester III pregnant women with the incidence of Pre-Eclampsia.